ChemInform Abstract: Palladium‐Catalyzed Three‐Component Coupling Reactions of 2‐(Cyanomethyl)phenol, Aryl Halides, and Carbon Monoxide. Issue 42 (October 2015) - Murai, Masahito; Okamoto, Kazuhiro; Miki, Koji; Ohe, Kouichi
Abstract Depending on the catalytic system, either 2‐amino‐ or 2‐aroylamino‐3‐aroylbenzofurans are obtained.